2011
DOI: 10.1186/2045-3701-1-42
|View full text |Cite
|
Sign up to set email alerts
|

Partners in crime: the TGFβ and MAPK pathways in cancer progression

Abstract: The TGFβ and Ras-MAPK pathways play critical roles in cell development and cell cycle regulation, as well as in tumor formation and metastasis. In the absence of cellular transformation, these pathways operate in opposition to one another, where TGFβ maintains an undifferentiated cell state and suppresses proliferation, while Ras-MAPK pathways promote proliferation, survival and differentiation. However, in colorectal and pancreatic cancers, the opposing pathways' mechanisms are simultaneously activated in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 79 publications
3
83
1
Order By: Relevance
“…MAPK activation and its over-expression play a crucial role in the progression of colorectal cancer (Chapnick et al, 2011). EGFR down regulation causes MAPK inhibition (Kumar et al, 2010), also MAPK has a key role in drug tolerance radiotherapy, our results indicated MAPK1 gene expression was decreased by c-Src inhibition; it seems c-Src downregulated MAPK1 expression by inhibiting the EGFRdependent manner.…”
Section: Discussionmentioning
confidence: 60%
“…MAPK activation and its over-expression play a crucial role in the progression of colorectal cancer (Chapnick et al, 2011). EGFR down regulation causes MAPK inhibition (Kumar et al, 2010), also MAPK has a key role in drug tolerance radiotherapy, our results indicated MAPK1 gene expression was decreased by c-Src inhibition; it seems c-Src downregulated MAPK1 expression by inhibiting the EGFRdependent manner.…”
Section: Discussionmentioning
confidence: 60%
“…Also we show that simultaneous use of PAMAM nanoparticle encapsulating c-Src and EGFR antisense had more than 50% inhibition effects on the c-Src, EGFR, MAPK1 and STAT5 expression. The important role of MAPK signaling pathway in cell cycle regulating and its role in the development of colon cancer has been determined (Chapnick et al, 2011). Also EGFR supperession cause MAPK inhibition that specified in other investigation (Kumar et al, 2010).…”
Section: Analysis the Combined Anti-egfr And C-src As-odn Effects On mentioning
confidence: 98%
“…Epidermal growth factor receptor activation by GPCR agonists to intracellular components depends on protein kinase and Calcium (Sabbah et al, 2008). MAPK signaling pathway plays a crucial role in the cell cycling regulation, also its over-expression and activation is essential for progression of colorectal cancer (Chapnick et al, 2011). STAT gene has role in the oncogenesis of various cancers, and also STAT5b involves in progression, cell cycling, migration, proliferation, gene expression and invasion in colon cancer (Yavari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that PSmadL attenuates R-Smad to inhibit its association with C-Smad which causes the negative regulation of TGF-β/Smad signaling by the MAPK pathway [19]. However, this argument cannot explain the opposite effect of the MAPK pathway on TGF-β/Smad signaling reported in several sources in the literature [1,9,[11][12][13]27].…”
Section: Potential Crosstalk Mechanismsmentioning
confidence: 99%
“…In a majority of human cancers carrying oncogenic Ras mutations, the activity rather than the levels of Ras expression is elevated. Thus, the levels of Ras activity are affected by the levels of MAPK activity, ultimately shaping the TGF-β response via crosstalk between Smad and the Ras-MAPK pathway [19].…”
mentioning
confidence: 99%